Antiproliferative activity of five garcinia species collected in Sabah, Malaysian Borneo against estrogen receptor-human breast carcinoma (MCF-7) cell line - N E Ahmad; M F Abu Bakar; Monica Suleiman; F I Abu Bakar; S F Sabran; F Kormin (2021)
Garcinia species are well-known for their unique properties of having natural secondary metabolite compounds called xanthone as well as their ethnomedicinal values such as antioxidant, anticancer, anti-inflammatory and antibacterial properties. The study was conducted to investigate the antiproliferative activity of peel, flesh and seed extracts of G. dulcis, G. parvifolia, G. nitida, G. mangostana var. mangosta and G. cambogia collected from Malaysian Borneo (Sabah) against estrogen receptor-positive human breast carcinoma (MCF-7) cells. The antiproliferative activity was assessed using 3-(4,5-dimethylthiazol-2-yl)-2,5diphenyltetrazolium bromide (MTT) assay. The results showed that G. dulcis seed induced strongest antiproliferative activity against MCF-7 cancer cell line with the IC50 value of 2.5±0.0 µg/ml, followed by G. dulcis flesh, G. mangostana var. mangostana peel and G. dulcis peel with IC50 values of 9.33 ± 3.21, 11.17 ± 1.04 and 17.67 ± 2.08 µg/ml, respectively. Meanwhile, the IC50 value for G. cambogia peel was 56.67 ± 10.5 µg/ml. No IC50 value was detected in all parts of G. parvifolia and G. nitida at concentration tested (<100 µg/ml). Overall, this study clearly showed that the whole fruit of G. dulcis displayed potent cytotoxic effect by inducing antiproliferative activity at low concentration. Further studies are needed in the future to develop this fruit as pharmaceutical and nutraceutical product for the treatment and prevention against cancer.